2022
DOI: 10.3390/nu14194133
|View full text |Cite
|
Sign up to set email alerts
|

The Diet Quality of Food-Insecure Australian Adults—A Nationally Representative Cross-Sectional Analysis

Abstract: Poor diet quality exacerbates risks for acute and chronic conditions. People experiencing food insecurity have an increased likelihood of lower diet quality; however, this has not been investigated in the Australian context. The aim of this cross-sectional study was to examine whether the diet quality of Australian adults differed according to their household food security status. Data were analysed from a nationally representative sample (≥19 years; n = 9115) collected as part of the National Nutrition and Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…In our study, nearly one in two households experienced some degree of food insecurity, and concerningly, and one in five households reported experiencing severe food Fig. 3 Proportion of respondents Australian Recommended Food Score (ARFS) scores categorised into four groups of diet quality: 'needs work' (< 33), 'getting there' (33)(34)(35)(36)(37)(38), 'excellent' (39)(40)(41)(42)(43)(44)(45)(46) or 'outstanding' (47þ) by food insecurity group insecurity which is characterised as skipping meals and experiencing hunger. Unlike other high-income countries, Australia lacks routine food insecurity measurement at national level which is one of the factors that hinders the prioritisation and implementation of effective interventions to support food-insecure Australians (37) .…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In our study, nearly one in two households experienced some degree of food insecurity, and concerningly, and one in five households reported experiencing severe food Fig. 3 Proportion of respondents Australian Recommended Food Score (ARFS) scores categorised into four groups of diet quality: 'needs work' (< 33), 'getting there' (33)(34)(35)(36)(37)(38), 'excellent' (39)(40)(41)(42)(43)(44)(45)(46) or 'outstanding' (47þ) by food insecurity group insecurity which is characterised as skipping meals and experiencing hunger. Unlike other high-income countries, Australia lacks routine food insecurity measurement at national level which is one of the factors that hinders the prioritisation and implementation of effective interventions to support food-insecure Australians (37) .…”
Section: Discussionmentioning
confidence: 66%
“…In terms of the impact of food insecurity on diet quality, this study reports similar findings to both national and international research. Within Australia, a recent study by Lindberg et al ( 41 ) reported that, on average, food-insecure adults (using a binary food security variable) had a three-point lower total diet quality score (using the dietary guideline index) when compared with food-secure Australians. However, this study was unable to determine food insecurity severity as it utilised a single-item measure, which has also been shown to underestimate food insecurity ( 42 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Food insecurity, the inadequate or insecure access to food due to financial constraints, is a growing concern in high-income countries like Australia (1) . Food insecure adults may have reduced diet quality due to constraints on food purchasing and consumption (2) but further research is needed to understand how the severity of food insecurity impacts diet quality in an Australian setting. This study aimed to examine the relationship between diet quality and increasing severity of household food insecurity using validated measurement tools.…”
mentioning
confidence: 99%